Paddington's adventures - Auerbach, Annie; Bond, Michael; Studio Canal; Heyday Films (2014)
Ever since the young bear Paddington entered the Browns' home, everything from having tea to taking the London Underground has been an incredible adventure.
At head of title: Paddington.
"Based on the new movie!"--Cover.
Guided reading level K.
Keywords: Paddington Bear -- (Fictitious character) -- Juvenile fiction; Paddington Bear -- (Fictitious character) -- Fiction; Bears -- Juvenile fiction; Adventure stories; Bears -- Fiction; Adventure and adventurers -- Fiction; Adventure stories; Bears; Paddington Bear (Fictitious character); Fiction; Juvenile works